Enhancing CO₂ selectivity in MOFs through a dual-ligand strategy: Experimental and theoretical insights - Amir Kazemi; Akram Karbalaee Hosseini; Mahyar Ashourzadeh Pordsari; Mohsen Tamtaji; Saber Keshavarz; Faranak Manteghi; Azadeh Tadjarodi; Ahad Ghaemi; Sohrab Rohani; William A. Goddard (Journal of CO2 Utilization)
Carbon dioxide (CO₂) is a primary greenhouse gas, playing a significant role in global warming and climate change. In response, metal-organic frameworks (MOFs) have emerged as effective materials for CO₂ capture. This study focuses on the synthesis and characterization of mono and heterometallic Cd and Zn MOFs [Zn₂(DPTTZ)(OBA)₂] (IUST-2), [Cd(DPTTZ)(OBA)] (IUST-3), and [Cd₂Zn(DPTTZ)₀.₅(OBA)₃(H₂O)(HCOOH)] (IUST-4). A dual-ligand strategy was employed using 4,4′-oxybis(benzoic acid) (OBA) and 2,5-di(pyridine-4-yl)thiazolo[5,4-d]thiazole (DPTTZ), with OBA acting as a rigid linker and DPTTZ providing nitrogen and sulfur heteroatoms to enhance gas adsorption. The presence of thiazole rings improves CO₂ selectivity through π-electron interactions and coordination with metal centers, contributing to higher adsorption efficiency. A sonochemical method was used to synthesize the MOFs, ensuring fast, eco-friendly production with uniform crystal growth. Among the synthesized MOFs, IUST-4 exhibited the highest CO₂ adsorption capacity, capturing 168 cm³ /g at 25°C. This superior performance is attributed to the synergistic interaction of Cd and Zn, which strengthens the coordination between CO₂ molecules and open metal sites. In addition, to validate the data and improve the analysis, theoretical studies indicated moderate interactions between CO₂ and the metal centers. These analyses were confirmed based on the Langmuir isotherm and Elovich kinetic models (R² > 0.95). Furthermore, DFT calculations revealed that IUST-4 exhibits the highest adsorption energy (-0.11 eV), outperforming IUST-2 (-0.06 eV) and IUST-3 (-0.05 eV). Additionally, IUST-4 maintained 86.1 % efficiency after ten adsorption-desorption cycles, demonstrating its stability and potential for industrial CO₂ capture applications. Overall, these findings highlight the potential of IUST-4 as a highly effective material for advancing CO₂ capture technologies in industrial applications.